Invasive fungal infections in pediatric patients with central nervous system tumors: novel insights for prophylactic treatments? - Dassi, Natália; Cappellano, Andrea Maria; Silva, Adriana Maria Paixão de Sousa da; da Silva, Nasjla Saba; Carlesse, Fabianne Altruda de Moraes Costa (Frontiers in Oncology, 2023)
Background and aims Invasive fungal disease (IFD) poses significant morbidity and mortality risks, especially in pediatric patients with neoplastic diseases. However, there is a notable lack of data concerning patients with central nervous system (CNS) tumors. Considering vulnerability factors to infections such as neutropenia, corticosteroids, chemotherapy, surgical interventions, and others, this study aims to evaluate the incidence of IFD in pediatric patients with CNS tumors and determine appropriate indications for prophylactic measures. This is a single-center, retrospective study conducted between 2011 and 2022 at the Pediatric Institute of Oncology (IOP-GRAACC-UNIFESP). Results A total of 38 cases of IFD were diagnosed in 818 children with CNS malignancies (4,6%). The mean age was 3.5 years (0.4-28y), with 22 (57.9%) male patients. Embryonal tumors (18/38, 47.3%) were the most prevalent CNS tumors, followed by low-grade gliomas (13/38, 34.2%). All episodes met the EORTC IFD criteria, and 36/38 (94.7%) were proven. Invasive yeast infections (33/36, 91.6%), predominantly Candida (30/33, 90.9%), were the most common diagnosis. In total, 25 patients (25/38, 65.8%) were receiving chemotherapy, with 13 of them having embryonal tumors. A total of 11 infants were in the Head Start scheme, resulting in a high prevalence of IFD in these group of patients (11/58, 18.9%). In total, 13 (13/38, 34.2%) patients underwent neurosurgery, mostly ventricular-peritoneal shunts revisions (10/13, 76.9%). Nine (9/38, 23.7%) were with prolonged use of corticosteroids, eight of them associated with neurosurgery. Conclusion Routine systemic antifungal prophylaxis based solely on diagnosis is not recommended for low-risk cases. Evaluating patient- and treatment-specific risk factors is crucial in infants undergoing high-dose chemotherapy with expected neutropenia and in patients requiring prolonged corticosteroid therapy alongside neurosurgical procedures.